Assessing the effectiveness of a cadaveric workshop in improving resident physicians’ confidence in performing ultrasound-guided joint injections - Thornton, Jane; Mahdi, Ahmed; Schultz, Lydia; Briscoe, Graham (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Implication StatementOur study showed that an educational workshop using a cadaveric specimen is effective in improving resident physicians’ confidence in performing ultrasound-guided, as well as landmark-based, joint injections. Participants also reported a strong interest in future cadaveric workshops on ultrasound-guided joint injections and believe such workshops would be a valuable educational resource for other physicians. Implementing cadaver-based ultrasound-guided joint injection workshops similar to the one discussed in this manuscript could be used to supplement training for these procedures in medical education and provide residents with the early experience they need to be able to perform these injections independently in clinic settings.